Fetal and Infant Effects of Maternal Opioid Use during Pregnancy: A Literature Review including Clinical, Toxicological, Pharmacogenomic, and Epigenetic Aspects for Forensic Evaluation - Elena Giovannini; Maria Paola Bonasoni; Jennifer Paola Pascali; Carla Bini; Guido Pelletti; Alberto Gualandi; Giovanni Dal Lago; Andrea Mercati; Beatrice Mariotti; Giulia Paola Pasini; Iarina Alexandra Poll; Paolo Fais (Children, 2024)
The two primary classes of opioid substances are morphine and its synthetic derivative, heroin. Opioids can cross the placental barrier, reaching fetal circulation. Therefore, at any gestational age, the fetus is highly exposed to pharmacologically active opioid metabolites and their associated adverse effects. This review aimed to investigate all the studies reported in a timeframe of forty years about prenatal and postnatal outcomes of opioid exposition during pregnancy. Clinical and toxicological aspects, as well as pharmacogenetic and epigenetic research focusing on fetal and infant effects of opioid use during pregnancy together with their medico-legal implications are exposed and discussed.